(untitled) (Journal of Patan Academy of Health Sciences, 2021)
Surgical management of vaginal agenesis constitutes a significant technical challenge. The goal of vaginal reconstruction is to create a neovagina that is both functionally and aesthetically satisfactory using a simple and reliable technique applicable to most. Bilateral pudendal thigh flaps were used to reconstruct neovagina for a 13-y girl with congenital vaginal agenesis. She presented with cyclical abdominal pain and hematometra, had normal secondary sexual characteristics and grossly normal external genitalia with a dimpling at the site of the vaginal orifice without lower vaginal tract.